An industrial experience report on the challenges in training localization and internationalization testers - Couto, Maria; Miranda, Breno (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2023: Anais do VIII Simpósio Brasileiro de Testes de Software Sistemático e Automatizado, 2023)
Localization (l10n) and internationalization (i18n) testing are crucial to a software that has been through the process of globalization (g11n) since most of the failures found with this strategy are highly visible for the end user. However, this practice faces some challenges when compared to other testing strategies. One of them is the lack of supporting material in literature and online, that directs affect the training of novice testers for this practice. This is awful because to assure the software’s quality the tester must be well trained. In the context were this study was performed, the training of novice l10n and i18n testers is conducted using the official test suite and software version. The problem with this approach is that by using the stable version of the software the tester might complete the training stage without observing in practice any l10n and i18n failure. This work reports the results and findings from a study conducted with l10n-trainer tool [3] in this industrial setting. The tool seeds l10n and i18n faults in Android applications. The seeded apps were used on the training two novice l10n and i18n testers to assure that during the training stage the testers had contact with l10n and i18n failures. By using l10n-trainer, we noticed that the novice tester that used the tool before run the traditional training test suite could report 6 new issues on the official software, whilst the other tester that followed the traditional training could not report any.